Antioxidant Properties of Flavonoids and Honeys Studied By Optical Spectroscopy Methods - Wybranowski, Tomasz; Ziomkowska, Blanka; Kruszewski, Stefan (Medical and Biological Sciences, 2014)
Flavonoids are considered very efficient radical scavengers and found in almost every plant. Antioxidant activities of flavonoids and a few popular kinds of bee honeys were investigated using absorbance spectroscopy. Spectral methods are powerful tools for the study of biologically active compounds and allow measurements of low concentrated substances under physiological conditions. Quercetin, naringenin, catechin, 3-hydroxyflavone were studied during the reaction with the 2,2-diphenyl-1- picrylhydrazyl radical (DPPH·). The results suggest that quercetin and catechin are better antioxidants than vitamin C. Among the analyzed honeys buckwheat honey exhibited the strongest antioxidant properties. Kinetic studies of the radical-scavenging activity were also performed. One can observe that popular vitamin C reduces free radicals instantly after adding to the solution, while flavonoids cause rather an exponential decay in concentration of the free radicals in the solutions. Our results show that adding of CuCl2 to the solution of DPPH and quercetin did not influence the level of antioxidant capacity of quercetin.